Personality Traits Needed by Remedial Reading Teachers - David Hurt; Elnora O. Roane; Earline M. Simms; Leo M. Schell (Educational Considerations, 1975)
A survey of Kansas reading teachers found that merely meeting the State Department of Education certification requirements is not sufficient to qualify a person to teach remedial reading. Administrators need to consider such personality traits as understanding and tolerance. This study found that remedial reading teachers need an extraordinary amount of patience and optimism.